Revised teaching and learning approaches in PC-based exercise - Narayanan, Dilip (Improving University Science Teaching and Learning, 2023)
This project report has been carried out in relation to the teaching course (Universitetspædagogikum JAN 2021) conducted from January 2021 to January 2022. The project suggest new teaching methods to SFAB20021U Molecular Pharmacology course which I have been involved as a teacher for the past 3 years. This Molecular Pharmacology course offers once a year in spring for the bachelor students. According to the course description they will learn basic theories, methodologies used in molecular pharmacology and how to integrate molecular biology, pharmacology techniques to elucidate the key role that plays in drug discovery process. This course offers students the opportunity to learn about Molecular Pharmacology in theory and practice.